Multi-omics profiling of sodium-overload (NECSO) programs identifies NEK8 as a central driver of colorectal cancer progression through single-cell and spatial transcriptomics - Ji, Yanchao; Yu, Bo; Yin, Xuedong; Yu, Tianqi; Wu, Xu; Zhao, Zongrui; Wang, Zheng; Gao, Xiangjie; Zhao, Jiajun; Fang, Zhihao; Wang, Yaxuan; Yu, Yingnan (Frontiers in Immunology, 2026)
BackgroundColorectal cancer (CRC) is a leading cause of cancer-related death, often marked by intratumoral heterogeneity, immune evasion, and therapeutic resistance. Recent advancements in single-cell and spatial transcriptomics have enabled a deeper understanding of the tumor microenvironment (TME), revealing key insights into metabolic reprogramming and immune suppression. This study focuses on the role of sodium-overload cell death (NECSO) and its interaction with immune modulation in CRC pathogenesis.MethodsWe employed an integrated multi-omic approach combining single-cell RNA-sequencing (scRNA-seq) and spatial transcriptomics (ST) to identify key NECSO-related genes in CRC. Through differential expression analysis and LASSO-Cox regression modeling, we developed a NECSO-based prognostic model. We validated our findings using TCGA and GEO datasets, assessing immune infiltration and spatial gene localization to determine the relationship between NEK8 and immune modulation.ResultsOur NECSO-derived five-gene signature (NEK8, DRD4, EPHB2, CYTH2, ACOT11) effectively stratified CRC patients into high- and low-risk groups. High-risk patients exhibited reduced immune cell infiltration, particularly CD8+ T cells, and showed poorer survival outcomes. Single-cell and spatial data confirmed the upregulation of NECSO activity in malignant epithelial cells and its association with immune suppression. NEK8, a central driver in the NECSO program, was significantly overexpressed in CRC and correlated with poor prognosis. Functional assays revealed that NEK8 knockdown inhibited CRC cell proliferation, migration, and invasion, reinforcing its potential as a therapeutic target.ConclusionsThe NECSO-derived signature provides a novel prognostic tool that integrates immune evasion and metabolic reprogramming in CRC. NEK8 plays a pivotal role in shaping the immune landscape and could serve as a biomarker for immunotherapy response, offering a pathway for personalized treatment strategies in precision oncology.